Administrativní areál v Praze - Hostivař, příprava a organizace výstavby objektu - Smolková, Pavlína (Vysoké učení technické v Brně. Fakulta stavební, 2013)
Závěrečná práce je zpracována pro administrativní areál v Praze. Jedná se o přípravu a organizaci výstavby objektu v Hostivaři. V práci je řešeno zařízení staveniště na nejdůležitější technologické etapy, ekonomické srovnání jeřábů, finanční a časové zhodnocení stavby, výběr hlavních mechanismů a textová část zabývající se charakterem stavby, jejími technickými údaji, postupem výstavby objektu a celkovým pojednáním o budově. Technologický předpis je zpracován pro technologickou etapu výstavby montovaného skeletu.

Final work is processed for an administrative center in Prague. It is the preparation and organization of the construction of the object in Hostivař. The work is done for the most important technological phases of site equipment, economic comparison of cranes, financial and time evaluation of building, selection of main mechanisms and main part of the text dealing with the character of the building, its technical data, process of constructing the object and the overall treatise about building. Technological process is made for the technological phase of construction of assembled skeleton.
Administrative grounds in Prague - Hostivař, preparation and organization of building construction
Keywords: Montovaný skelet; hlubinné zakládání; strojní sestava; limitky zdrojů; ekonomické srovnání; zařízení staveniště; harmonogram; rozpočet; Prefabricated skeleton; deep foundations; assembly of machines; limits of resources; economic comparison; site equipment; schedule; budget